2015
DOI: 10.1039/c4nr06119e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a refractive index and an extinction coefficient of standard production of CVD-graphene

Abstract: The refractive index and extinction coefficient of chemical vapour deposition grown graphene are determined by ellipsometry analysis. Graphene films were grown on copper substrates and transferred as both monolayers and bilayers onto SiO 2 /Si substrates by using standard manufacturing procedures. The chemical nature and thickness of residual debris formed after the transfer process were elucidated using photoelectron spectroscopy. The real layered structure so deduced has been used instead of the nominal one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…Combination of the Drude model with the Lorentz line was proposed for description of the optical parameters of graphene [16]. The pure Drude model gave not so satisfactory results in our case, but its accomplishing by one Lorentz line remarkably improved the situation.…”
Section: Spectroscopic Ellipsometrymentioning
confidence: 97%
“…Combination of the Drude model with the Lorentz line was proposed for description of the optical parameters of graphene [16]. The pure Drude model gave not so satisfactory results in our case, but its accomplishing by one Lorentz line remarkably improved the situation.…”
Section: Spectroscopic Ellipsometrymentioning
confidence: 97%
“…The original intent of Vakil and Engheta's model was to simulate graphene in commercial electromagnetic software; it was emulated with tremendous success by researchers working on device simulations thereafter [37,38,[41][42][43]. Later, experimental optics researchers also successfully adopted this model to fit their experimental measurements of graphene's refractive index [44][45][46][47][48][49]. It should be noted that the rapid development of graphene research has prompted improvement in modern Maxwell solvers to incorporate surface current boundary conditions for simulation of graphene's 2D optical conductivity in 3D devices [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…As it is already known, by using this method, the graphene layer could be damaged or end up unintentionally with a higher doping level due to several agents present at the different steps (such as Cu etchant, dust particles, water molecules or PMMA residues) degrading its final electronic mobility [Capasso et al 2014, Leclercq. J et al 2016 or changing its optical properties [Ochoa-Martinez et al 2015]. Moreover, previous reports indicate that not only PMMA can be a p-type dopant on graphene [Chen et al 2007, Na et al 2006] but it has been also reported that the presence of oxygen may also influence the p-type doping level [Ryu et al 2010].…”
Section: The Ies-upm Graphene Transfer Processmentioning
confidence: 99%
“…With the aim of exploring the evolution of the surface composition on top of and under the graphene layer, measurements were made at three different take-off angles (10º, 45º and 90º, outing photoelectrons pathway measured from the sample surface), changing thus the explored depth. Further information and details on ARXPS measurements can be obtained in [Ochoa-Martinez et al 2015].…”
Section: Process Characterizationmentioning
confidence: 99%
See 1 more Smart Citation